Perancangan Sistem Penjualan Berbasis Web pada Kedai Rio Bersaudara - Dewi, Ria Sastra; Kurniati, Rezki (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of information technology has pushed Micro, Small, and Medium Enterprises (MSMEs) to innovate in order to remain competitive. Kedai Rio Bersaudara, which has been operating for 20 years, still uses a manual system for sales and inventory management, resulting in delays in transaction recording, data errors, and difficulties in generating reports. This study aims to develop a web-based sales system using the Rapid Application Development (RAD) method to integrate business processes efficiently and accurately. The system is built with PHP and MySQL using the Laravel framework, featuring transaction recording, inventory tracking for incoming and outgoing goods, and real-time report generation. The results show that the system improves operational efficiency, reduces recording errors, and facilitates monitoring of sales and inventory. This system enables business owners to make faster and more accurate decisions, ultimately increasing productivity and competitiveness.